Fullerene up-take alters bilayer structure and elasticity: A small angle X-ray study. (May 2015) - Drasler, Barbara; Drobne, Damjana; Sadeghpour, Amin; Rappolt, Michael
Graphical abstract: Highlights: Exposure to fullerenes (C60 ) can lead to damaging effects on biomembranes. C60 causes increase in the bilayer undulations (∼20%). C60 enhances the mean inter-bilayer separation (∼15%). C60 -incorporation increased the linear expansion coefficient. Addition of C60 causes a drop in the bending rigidity of the bilayers (20–40%). Abstract: The coupling of fullerene (C60 ) to the structure and elasticity of 1-palmitoyl-2-oleoyl- sn -glycero-3-phosphocholine bilayers has been explored by synchrotron small angle X-ray scattering. Multilamellar vesicles were loaded with 0, 2 and 10 mol.% of C60 and studied in a temperature range from 15 to 65 °C. The addition of C60 caused an increase in the bilayer undulations (∼20%), in the bilayer separation (∼15%), in the linear expansion coefficient and caused a drop in the bending rigidity of the bilayers (20–40%). Possible damaging effects of fullerene on biomembranes are mainly discussed on the basis of altered bilayer fluidity and elasticity changes.